Analysis of trends in the historical series of precipitation and flow stay curve in Cachoeira do Piriá, Pará (Research, Society and Development, 2021)
Northern Brazil has high rainfall, which is related to the presence of the Amazon rainforest. In view of this, it is necessary that studies that analyze the hydrological behavior in hydrographic basins of this region be developed, since these can be used, later, as tools and bases for other types of studies or for analyzing the viability of works in general. Two of the main components of the hydrological cycle are precipitations and flows from water bodies. In this way, the present research carried out an analysis about the code pluviometric station (146008) and code fluviometric station (32620000), both located in the municipality of Cachoeira do Piriá, state of Pará, with the objective of analyzing the influence of precipitations in the river flows in the hydrographic basin through the construction of a hietogram, also carrying out the assessment of normal climatology and trend for the historical series of rain data, using the Linear, Mann Kendall and Sen´s Slope methods. For the flow data, the permanence curve was elaborated. Finally, it was observed, from the pluviometric data, that the precipitation in the municipality does not present a trend and, from the fluviometric data, it was possible to observe that its flow in 95% of the cases is, approximately, 200 m³ / s.